Hypertension in Hypoxia - Chawla, Sheetal; Singhal, Rashi; Guchhait, Prasenjit (Journal of Hypertension and Cardiology, 2014)
An overview of blood pressure regulation in hypoxia addresses altitude physiology, sleep disordered breathing, and cardiopulmonary disease. It reviews pathophysiology and therapeutic implications.
Keywords: hypertension; hypoxia